The effectiveness of continuous batch column in wasra system to treat the groundwater at Universiti Malaysia Pahang - Suhaili, Kamaruddin (2014)
Water is a chemical compound that is liquid at normal pressure and at room temperature. Water contains 70% of the earth's surface. Every life on this planet needs water to survive. Water can also exist in three forms such as ice (solid), water (liquid) and steam (gas). Based on Sumber Air Negara (MSAN) on 1982, monsoon season every year saturates with more than 990 billion m 3 of rainfall. Of this amount 6.5% or 64 billion m 3 remain in the groundwater. Due to the country's water resources are abundant, the total population increased from recent years. Increasing population causing pollution to the water sources. WASRA system is one of the systems that we use to treat the groundwater before supply clean water to the community. The aim of this study to determine the effectiveness of the batch column unit in WASRA Pretreatment process to reduce groundwater contaminants and the removal of contaminants from groundwater through a continuous batch column in WASRA system. Sample from WASRA system before and after through the continuous Batch column will be tested based on eleven parameter referred to the "Standard Method for the Examination of Water and Wastewater" (21th Edition ) by American Public Health Associate (APHA, 2005). Analysis of data was performed by using a 1-way analysis-of-variance (1-way ANOVA). The significant ANOVA (P<0.05) studies shown the different in value of the monitored eleven parameters which indicates the data obtained is accurate. Water sample was taken from groundwater resources near to Mosque at University Malaysia Pahang. The result gained is relevant with the previous study on the same field. For the physical parameters, the removal efficiency for Turbidity and Total suspended solid is 79%, 79% respectively. The results for heavy metal test also showed the decreasing in its concentration. Percentage of removal for Zinc and iron is 71%, 67% respectively. Other parameters is hardness, conductivity, BOD 5 , COD and manganese is 74%, 10%, 45%, 72%, 60% respectively. As a conclusion, the water is treated by Continuous Batch column in WASRA system is effectives to remove the groundwater contaminated at 95% and still acceptable to supply the clean water to the community.